The Impact of Tin Trade Governance Cases on Community Purchasing Power in Bangka Belitung Province: A Case Study on the Sustainability of MSME - Ghina Zhahira; Riko Erlima Putra; Sirlus Andreanto Jasman Duli; Mozaik Plamonia Ramadhan; Ezzy Syafitri (Jurnal Ragam Pengabdian, 2026)
Tin mining has long served as the economic backbone of Bangka Belitung Province, but governance disruptions in the tin trade have recently triggered socio-economic instability. This study aims to evaluate how tin trade governance cases have affected community purchasing power and the sustainability of micro, small, and medium enterprises (MSMEs) in the province. Employing a qualitative evaluative approach, data were collected through in-depth interviews, field observations, and document analysis. The study reveals a heterogeneous impact: while communities directly dependent on tin mining experienced sharp declines in purchasing power and business turnover, sectors less reliant on mining—such as smallholder coffee farming— demonstrated stronger resilience. Informal intermediaries initially buffered economic shocks but their sudden disappearance intensified local instability. The findings highlight the critical role of livelihood diversification in enhancing economic resilience and underscore the need for governance reforms to include socio-economic safeguards for affected communities. Overall, the study contributes to the literature on natural resource governance by providing micro-level insights into how governance crises propagate through local economies.